Synthesis and conformational studies of indolizines - George, Rosemary (Rhodes University, Faculty of Science, Department of Chemistry, 1994)
The present investigation has involved a kinetic and mechanistic study of the thermal cyclization of 3-acetoxy-3-(2-pyridyl)-2-methylenepropanoate esters and related compounds to 2-substituted indolizines. Substrates for the kinetic study were prepared via the Baylis-Hillmann reaction of pyridine-2-carboxaldehydes with acrylate esters, acrylonitrile and methyl vinyl ketone. The resulting hydroxy compounds were then acetylated to afford the acetoxy derivatives, thermal cyclization of which gave the corresponding 2-substituted indolizines. The cyclization reactions was followed using 'H NMR spectroscopy and were shown to follow firstorder kinetics. The influence of the various substituents on the observed first-order rate constants has been examined and variable temperature studies have permitted evaluation of activation parameters for the formation of methyl indolizine-2-carboxylate and ethyl indolizine-2-carboxylate. An alternative route to 2-substituted indolizines via halogenated derivatives was explored and several halogenated 2-pyridyl derivatives were synthesised and their thermal cyclization to indolizines was attempted. Novel 5-methylindolizine-2-carboxamides were prepared as part of this investigation and dynamic NMR spectroscopy was used to study internal rotation about the amide N-CO bond in these compounds.
Keywords: Indole alkaloids -- Research; Organic compounds -- Synthesis; Chemistry, Organic